COMPETENCY-BASED FOUNDATIONS FOR PREPARING FUTURE PRIMARY SCHOOL TEACHERS FOR CLASS TEACHER ACTIVITIES - Khusenova Sadaqat Botirovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the competency-based foundations for preparing future primary school teachers for class teacher activities. In the modern education system, a class teacher acts not only as a pedagogue who organizes the educational process but also as an important stakeholder who establishes cooperation among students, parents, and the community. Therefore, the formation of professional, communicative, organizational, and educational competencies necessary for class teacher activities in future teachers is one of the urgent issues of contemporary teacher education. The study examines the theoretical foundations of the competency-based approach, the structural components of preparation for class teacher activities, and the mechanisms for their development. The research findings demonstrate that the competency-based approach is an effective means of improving future teachers’ readiness for class teacher responsibilities.